Reykjanes Peninsula, Iceland, as an Analog Site for Venus; Remote Sensing Investigation and Planned Field Work to Support the VERITAS Mission - Adeli, Solmaz; Domac, Akin; Mueller, N; Nunes, Daniel; Garland, Stephen Patrick; Helbert, Jörn; Dyar, M. D.; Hauber, Ernst; Alemanno, Giulia; Younis, Marwan; Gilmore, M.; Hensley, Scott; et al. (2023)
One of the main objectives of the NASA VERITAS and ESA EnVision missions is to characterize the composition and origin of the major geological terrains on Venus. The best dataset of surface composition covering the southern hemisphere of Venus comes from the VIRTIS instrument on board the Venus Express mission, which used a near-infrared sensor [1, 2, 3]. It mapped the Venusian surface through narrow atmospheric windows at 1.02, 1.10 and 1.18 μm [4, 5]. Because the dense CO2 atmosphere of Venus only allows observations in narrow spectral windows around 1 μm, knowledge of the mineralogy of Venus’ surface must be based at that wavelength [6]. Although the VIRTIS data showed that Venus had undergone recent volcanic activity [7], the limited spectral resolution and the dense atmosphere of Venus prevented this instrument from revealing more details. The future VERITAS and EnVision missions will be able to observe the surface of Venus through five atmospheric windows with six bands. These will enable the spectral characteristics of the Venusian surface, as well as the type of lava and likely alteration processes, to be determined in unprecedented detail.